Professor Jan Oderfeld - K. KĘDZIORA (Engineering Transactions, 2014)
The Laudatio speech delivered during the ceremony of awarding Prof. Jan Oderfdeld an honorary doctorate by Warsaw University of Technology and on the occasion of his 100th birthday